2007
DOI: 10.1186/1471-2466-7-8
|View full text |Cite
|
Sign up to set email alerts
|

Can asthma control be improved by understanding the patient's perspective?

Abstract: BackgroundClinical trials show that asthma can be controlled in the majority of patients, but poorly controlled asthma still imposes a considerable burden. The level of asthma control achieved reflects the behaviour of both healthcare professionals and patients. A key challenge for healthcare professionals is to help patients to engage in self-management behaviours with optimal adherence to appropriate treatment. These issues are particularly relevant in primary care, where most asthma is managed. An internati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
158
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 176 publications
(164 citation statements)
references
References 57 publications
0
158
0
6
Order By: Relevance
“…This is important in clinical practice because these patients need to have their treatment reviewed as well as addressing risk factors for poor asthma control. 30 A study of 382 patients in Hong Kong found that the ACT could predict step-up of asthma therapy in 70.2% of consultations, 13 suggesting that this tool could actually assist doctors' treatment decisions. Indeed, Ko et al found that the ACT correlates better with treatment decisions made by asthma specialists than spirometry, PEF, or fractional exhaled nitric oxide measurements.…”
Section: -9mentioning
confidence: 99%
“…This is important in clinical practice because these patients need to have their treatment reviewed as well as addressing risk factors for poor asthma control. 30 A study of 382 patients in Hong Kong found that the ACT could predict step-up of asthma therapy in 70.2% of consultations, 13 suggesting that this tool could actually assist doctors' treatment decisions. Indeed, Ko et al found that the ACT correlates better with treatment decisions made by asthma specialists than spirometry, PEF, or fractional exhaled nitric oxide measurements.…”
Section: -9mentioning
confidence: 99%
“…[32][33][34] Therefore, it has been suggested that health professionals should routinely try to elicit patients' beliefs about their condition. [39][40][41] Misperceptions that might affect health outcomes may be detected and can then be addressed and treatment or self-management negotiated. In a recent quasi-experimental study, GPs received training for 6 hours in ways to elicit patients' illness beliefs.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…3 There is evidence that clinicians frequently over-estimate asthma control and under-estimate the impact of asthma on patents' lives. [4][5][6] The British Thoracic Society and Scottish Intercollegiate Guidelines Network UK guidelines for the management of asthma 7 recommend that the Royal College of Physicians (RCP) '3 questions' 8 should be asked at all asthma clinical assessments to assess patient morbidity. This simple, quick, and easy-to-use questionnaire has, however, never been validated as a useful tool for routine clinical practice.…”
Section: Introductionmentioning
confidence: 99%